2001
DOI: 10.1525/sop.2001.44.3.263
|View full text |Cite
|
Sign up to set email alerts
|

From Appealing to Appalling: Disenchantment With a Romantic Partner

Abstract: This study examines the tendency for there to be similarities between the qualities that initially attract individuals to romantic partners and those they later dislike, that is, "fatal attractions." Approximately 44 percent of the individuals in this sample of 125 dating persons experience fatal attractions. Individual cases illustrate opposing themes, such as "nice to passive" and "strong to stubborn." One-third (33.7%) of the respondents themselves identify similarities between attracting and disliked partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
(15 reference statements)
1
7
0
Order By: Relevance
“…Shifts in impressions, though not inevitable, occur quite frequently in developing relationships, as seen in recent studies of roommate relationships, romantic relationships, and work relationships (Felmlee, 2001;Paulhus, 1998;Swann et al, 2000;Ybarra, 2001). The results of the present studies suggest that Big Five impressions diVer in their upward and downward mobility.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Shifts in impressions, though not inevitable, occur quite frequently in developing relationships, as seen in recent studies of roommate relationships, romantic relationships, and work relationships (Felmlee, 2001;Paulhus, 1998;Swann et al, 2000;Ybarra, 2001). The results of the present studies suggest that Big Five impressions diVer in their upward and downward mobility.…”
Section: Discussionsupporting
confidence: 74%
“…In many cases, Wrst impressions turn into lasting ones, through a mix of initial accuracy, information-processing biases, and/or self-fulWlling prophecies (De La Ronde & Swann, 1998;Kunda, 1999;Murray, Holmes, & GriYn, 1996). Nevertheless, it is also common for impressions to change over the course of acquaintanceship, at times demonstrating dramatic reversals (Felmlee, 2001;Paulhus, 1998;Ybarra, 2001). The study of when and why impressions change, we believe, is an essential complement to research on when and why impressions persist.…”
mentioning
confidence: 95%
“…Felmlee (2001) posited a "fatal attraction" hypothesis for this influence of time on the perception of personality traits: certain traits that attract a young woman to a young man in the beginning of the relationship may repel her from the same young man as the relationship continues or sours over time. The five most common attractive to unattractive trait pairs found were nice to passive, strong to stubborn, funny to "flaky," outgoing to "over the top," and caring to clingy (Felmlee, 2001). The "fatal attraction" hypothesis may be used to explain why a young woman who was initially attracted to her nice guy because she thought he was "nice," over time may become eager to dump him because she views him as "too nice" (i.e., passive).…”
mentioning
confidence: 99%
“…In fact, Felmlee (2001) found that the very things that attract us to a romantic partner often turn sour with the passage of time. The kind and gentle man gets seen as a wimp; the strong, silent type is seen as a tyrannical bore.…”
Section: Disillusionmentmentioning
confidence: 99%